Emotional climate and high quality learning experiences in science teacher education. Issue 10 (18th August 2014) - Bellocchi, Alberto; Ritchie, Stephen M.; Tobin, Kenneth; King, Donna; Sandhu, Maryam; Henderson, Senka
Abstract The role of emotion during learning encounters in science teacher education is under‐researched and under‐theorized. In this case study, we explore the emotional climates (ECs), that is, the collective states of emotional arousal, of a preservice secondary science education class to illuminate practice for producing and reproducing high quality learning experiences for preservice science teachers. Theories related to the sociology of emotions informed our analyses from data sources such as preservice teachers' perceptions of the EC of their class, emotional facial expressions, classroom conversations, and cogenerative dialogue. The major outcome from our analyses was that even though preservice teachers reported high positive EC during the professor's science demonstrations, they also valued the professor's in the moment reflections on her teaching that were associated with low EC ratings. We co‐relate EC data and preservice teachers' comments during cogenerative dialogue to expand our understanding of high quality experiences and EC in science teacher education. Our study also contributes refinements to research perspectives on EC. © 2014 Wiley Periodicals, Inc. J Res Sci Teach 51: 1301–1325, 2014.